The Phenomenon of Shooting Stars from the Perspective of Science and the Qur'an: Integrating Students Building Character - Novi Ayu Kristiana Dewi; Nurlela; Mufid Masngudi (Attractive : Innovative Education Journal, 2025)
The article aims to understand the differences between asteroids and meteorites, identify the causes of meteor formation, and analyze the mechanisms by which Earth protects itself from collisions with extraterrestrial objects. Furthermore, the research explores the phenomenon of shooting stars from both a scientific perspective and the teachings of the Quran. This study employs a literature review method with a qualitative descriptive approach, in which data are collected from various sources, including previous research, books, and the Quran. The data analysis process involves filtering relevant information according to the research theme, presenting it narratively, and drawing conclusions. The findings indicate that asteroids and meteorites are distinct celestial bodies in terms of their location and size. Meteoroids are more likely to enter Earth's atmosphere, where friction causes partial or complete combustion, producing the luminous effect known as meteors or shooting stars. From a theological perspective, meteors are associated with arrows used to prevent jinn from eavesdropping on divine matters. Therefore, it is inappropriate to associate God with this natural phenomenon by requesting or invoking shooting stars. In a religious context, humans are expected to follow divine commandments by worshiping God alone. Consequently, integrating the values of faith and devotion into science education is essential, as scientific knowledge and the teachings of the Quran have never been proven to be in conflict.